Diagnosis of cervical cancer by a urine test - Łopuszyńska, Anna Małgorzata; Pawlicki, Bartłomiej; Pawlicki, Mateusz Maciej; Lorenc, Karol; Kozioł, Magdalena; Misztal, Zofia (Journal of Education, Health and Sport, 2019)
Cervical cancer is the fourth most common malignant tumor among women in the world. However, 90% of deaths occur in developing countries. Tumor pathogenesis is associated with exposure to high-risk human papillomavirus (hrHPV), most often 16 and 18 strains. The sooner precancerous lesions or cancer are detected, the higher the chance of survival is. That is why prophylaxis is so important in this case. Due to the low turnout of women in cytology, new, alternative methods of prevention are needed. According to the research, women prefer tests in which samples are taken by themselves. Hence, more and more studies on the use of urine in the prevention of cervical cancer. Urine is a material that is easy to pick up. Patients feel comfortable because they can do it by themselves. Still, more research is needed to optimize its collection, transport, or tests used on samples.